Math, asked by abhi16637, 1 year ago

plz solve this question guyzz I'll give uhh brain mark ​

Attachments:

Answers

Answered by Anonymous
2

  \underline{\underline{\bf{{ prove \: that}}}} :  -  \\  \\  {tan}^{ - 1} x +  {tan}^{ - 1} \frac{2x}{1 -  {x}^{2} }   =  {tan}^{ - 1}  \frac{3x -  {x}^{3} }{1 - 3 {x}^{2} }  \\  \\   \underline{ \underline{\bf{step - by - step \: explanation}}} :  -  \\  \\

Formula used→

 \implies \:  {tan}^{ - 1} x +  {tan}^{ - 1} y =  {tan}^{ - 1}  \frac{x + y}{1 - xy}  \\  \\

Now , taking left hand side ( LHS)

 \rightarrow \:  {tan}^{ - 1} x +  {tan}^{ - 1}  \frac{2x}{1 -  {x}^{2} }  \\  \\ applying \: the \: given \: formula \:  \\  \\  \rightarrow \:  {tan}^{ - 1}  \bigg( \frac{x +  \frac{2x}{1 -  {x}^{2} } }{1 - x \times  \frac{2x}{1 -  {x}^{2} } }  \bigg) \\  \\  \rightarrow \:  {tan}^{ - 1}  \bigg( \frac{ \frac{x -  {x}^{3} + 2x }{1 -  {x}^{2} } }{1 -  \frac{2 {x}^{2} }{1 -  {x}^{2} } }  \bigg) \\  \\  \rightarrow \:  {tan}^{ - 1}  \bigg( \frac{ \frac{3x -  {x}^{3} }{1 -  {x}^{2} } }{ \frac{1 -  {x}^{2} - 2 {x}^{2}  }{1 -  {x}^{2} } }  \bigg) \\  \\  \rightarrow \:  {tan}^{ - 1}  \bigg( \frac{3x -  {x}^{3} }{1 - 3 {x}^{2} }  \bigg)

LHS = RHS

Hence proved.

Similar questions